Persistent Inequities in Intravenous Thrombolysis for Acute Ischemic Stroke in the United States: Results From the Nationwide Inpatient Sample - Philip Sun; Ling Zheng; Michelle Lin; Steven Cen; Gmerice Hammond; Karen E. Joynt Maddox; May Kim‐Tenser; Nerses Sanossian; William Mack; Amytis Towfighi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Despite its approval for acute ischemic stroke >25 years ago, intravenous thrombolysis (IVT) remains underused, with inequities by age, sex, race, ethnicity, and geography. Little is known about IVT rates by insurance status. Methods and Results We assessed temporal trends from 2002 to 2015 in IVT for acute ischemic stroke in the Nationwide Inpatient Sample using adjusted, survey‐weighted logistic regression. We calculated odds ratios for IVT for each category in 2002 to 2008 (period 1) and 2009 to 2015 (period 2). IVT use for acute ischemic stroke increased from 1.0% in 2002 to 6.8% in 2015 (adjusted annual relative ratio, 1.15). Individuals aged ≥85 years had the most pronounced increase during 2002 to 2015 (adjusted annual relative ratio, 1.18) but were less likely to receive IVT compared with 18‐ to 44‐year‐olds in period 1 (adjusted odds ratio [aOR], 0.23) and period 2 (aOR, 0.36). Women were less likely than men to receive IVT, but the disparity narrowed over time (period 1: aOR, 0.81; period 2: aOR, 0.94). Inequities in IVT resolved for Hispanic individuals in period 2 (aOR, 0.96) but not for Black individuals (period 2: aOR, 0.81). The disparity in IVT for Medicare patients, compared with privately insured patients, lessened over time (period 1: aOR, 0.59; period 2: aOR, 0.75). Patients treated in rural hospitals remained less likely to receive IVT than in urban hospitals; a more dramatic increase in urbanity widened the inequity (period 2, urban nonteaching versus rural: aOR, 2.58, period 2, urban teaching versus rural: aOR, 3.90). Conclusions IVT for acute ischemic stroke increased among adults. Despite some encouraging trends, the remaining disparities highlight the need for intensified efforts at addressing inequities.